2018
DOI: 10.14499/indonesianjcanchemoprev9iss1pp41-46
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between TGF-β/Smad Signalling and Tumorigenesis Arising from Clonorchis sinensis Induced Hepatic Fibrosis

Abstract: Clonorchiasis is a parasitic infection caused by food borne trematode, Clonorchis sinensis that is mainly prevalent in Asian countries, including South Korea, China, northern Vietnam, Japan, as well as far-eastern Russia, in which over 35 million people are the casualties. Clonorchiasis is characterized by the development of hepatic fibrosis. Upon chronic liver injury following the C. sinensis infection, hepatic fibrosis develops into cholangiocarcinoma with a concomitant genetic and epigenetic mutations. Chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…TGF‐β can simultaneously promote angiogenesis and antiangiogenesis, and these opposing effects depend on different TGF‐β receptors and the phosphorylation of different downstream SMADs 34 . SMAD1/5/8 phosphorylation via TGF‐β/ALK1 contributes to angiogenesis, whereas SMAD2/3 phosphorylation via TGF‐β/ALK5 inhibits angiogenesis and leads to blood vessel maturation 35 . In this study, we found that downregulation of NEAT1 could substantially inhibit the TGF‐β1 signaling pathway activation, with phosphorylation of SMAD1 and SMAD5 in HUVECs, which could serve as a potential method to promote angiogenesis in BS.…”
Section: Discussionmentioning
confidence: 99%
“…TGF‐β can simultaneously promote angiogenesis and antiangiogenesis, and these opposing effects depend on different TGF‐β receptors and the phosphorylation of different downstream SMADs 34 . SMAD1/5/8 phosphorylation via TGF‐β/ALK1 contributes to angiogenesis, whereas SMAD2/3 phosphorylation via TGF‐β/ALK5 inhibits angiogenesis and leads to blood vessel maturation 35 . In this study, we found that downregulation of NEAT1 could substantially inhibit the TGF‐β1 signaling pathway activation, with phosphorylation of SMAD1 and SMAD5 in HUVECs, which could serve as a potential method to promote angiogenesis in BS.…”
Section: Discussionmentioning
confidence: 99%